Transcriptional profiles of Burkholderia pseudomallei reveal the direct and indirect roles of Sigma E under oxidative stress conditions - Siroj Jitprasutwit (2018)
© 2014 Jitprasutwit et al.; licensee BioMed Central Ltd. Background: Burkholderia pseudomallei, the causative agent of melioidosis, is a Gram-negative bacterium widely distributed in soil and water in endemic areas. This soil saprophyte can survive harsh environmental conditions, even in soils where herbicides (containing superoxide generators) are abundant. Sigma factor E (σE) is a key regulator of extra-cytoplasmic stress response in Gram-negative bacteria. In this study, we identified the B. pseudomallei σEregulon and characterized the indirect role that σEplays in the regulation of spermidine, contributing to the successful survival of B. pseudomallei in stressful environments. Results: Changes in the global transcriptional profiles of B. pseudomallei wild type and σEmutant under physiological and oxidative stress (hydrogen peroxide) conditions were determined. We identified 307 up-regulated genes under oxidative stress condition. Comparison of the transcriptional profiles of B. pseudomallei wild type and σEmutant under control or oxidative stress conditions identified 85 oxidative-responsive genes regulated by σE, including genes involved in cell membrane repair, maintenance of protein folding and oxidative stress response and potential virulence factors such as a type VI secretion system (T6SS). Importantly, we identified that the speG gene, encoding spermidine-acetyltransferase, is a novel member of the B. pseudomallei σEregulon. The expression of speG was regulated by σE, implying that σEplays an indirect role in the regulation of physiological level of spermidine to protect the bacteria during oxidative stress.Conclusion: This study identified B. pseudomallei genes directly regulated by σEin response to oxidative stress and revealed the indirect role of σEin the regulation of the polyamine spermidine (via regulation of speG) for bacterial cell protection during oxidative stress. This study provides new insights into the regulatory mechanisms by which σEcontributes to the survival of B. pseudomallei under stressful conditions.